Transfusion in orthopaedic surgery. (2021) - Blankstein, A. R.; Houston, B. L.; Fergusson, D. A.; Houston, D. S.; Rimmer, E.; Bohm, E.; Aziz, M.; Garland, A.; Doucette, S.; Balshaw, R.; Turgeon, A.; Zarychanski, R.
No abstract available